Equipping Immigrants: Migration Flows and Capital Movements - Fabian Lange; Douglas Gollin (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
This paper explores the extent to which migration-related capital flows can explain the variation in investment rates and current and capital account imbalances across OECD countries. Migrants must be equipped with machines, and the resulting demands for capital are likely, all else being equal, to generate cross-border flows of capital. We analyze and test the empirical predictions of a simple model with endogenous capital and labor flows. This model allows for exogenous variation in the supply of migrant labor as well as in local production conditions. Empirically, the observed correlations in investment rates, capital and labor flows can best be explained by an inelastic supply of migrant labor and large exogenous variation in local production conditions over time compared to the exogenous variation in the supply of migrant labor. We then examine how much the increase in net migration rates contributed to the increase in the US current account deficit since 1960. Between 1960 and 2000, the US current account declined by about 4% of annual GDP. The increase in migration contributed about 1% of GDP to this decline.
Keywords: F21; F22; 330